Adaptive Extended Kalman Filter using Exponencial Moving Average⁎. Issue 25 (2018) - Silva, Jean Gonzalez; Aquino Limaverde Filho, José Oniram De; Feitosa Fortaleza, Eugênio Liborio
Abstract: This paper presents a novel adaptive extended Kalman filter for nonlinear discrete-time systems that deals with variations in the process noise covariance. The process noise covariance is estimated at each sample time by calculating the innovation term covariance through exponential moving average. Numerical simulations were carried out to illustrate the proposed algorithm based on a closed-loop nonlinear mass-spring-damper system.